2010
DOI: 10.1186/1472-6874-10-14
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre matched case control study of risk factors for Preeclampsia in healthy women in Pakistan

Abstract: BackgroundPreeclampsia is one of the leading causes of maternal and perinatal morbidity and mortality world-wide. The risk for developing preeclampsia varies depending on the underlying mechanism. Because the disorder is heterogeneous, the pathogenesis can differ in women with various risk factors. Understanding these mechanisms of disease responsible for preeclampsia as well as risk assessment is still a major challenge. The aim of this study was to determine the risk factors associated with preeclampsia, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
45
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 28 publications
16
45
3
3
Order By: Relevance
“…However, it was different from the results observed by other study [49] that observed the relationship between advanced maternal age and occurrence of preeclampsia. Such difference could be due to the variation of study designs and study settings.…”
Section: Discussioncontrasting
confidence: 56%
“…However, it was different from the results observed by other study [49] that observed the relationship between advanced maternal age and occurrence of preeclampsia. Such difference could be due to the variation of study designs and study settings.…”
Section: Discussioncontrasting
confidence: 56%
“…Mexican Spanish [5], Japanese [6], Chinese [7], Thai [8], Turkish [9], Arabic [10], Urdu (Pakistan language) [11], Lithuanian [12], Danish, Brazilian, Korean, Russian, Polish, Bulgarian, Hungarian, Italian, Hebrew [13]. Those international studies suggest that the psychometric properties of the scale are satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes in pregnancy is associated with elevated rates of miscarriage [83], pre-eclampsia [84,85], preterm labor, cesarean sections [86,87] and fetal malformation [86,[88][89][90]. Optimal glycemic control during pregnancy may reduce these diabetes-related risks, but a more effective time to intervene could be before pregnancy.…”
Section: Diabetesmentioning
confidence: 99%